2011
DOI: 10.1249/mss.0b013e31821ecf61
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses to Walking in Patients with Peripheral Artery Disease

Abstract: Purposes To assess the cardiovascular responses during constant load walking and to identify predictors of this response in peripheral artery disease (PAD) patients. Methods Seventy-nine patients with PAD performed a constant load treadmill test (2 mph, 0% grade). During the test, systolic blood pressure (BP), diastolic BP, and heart rate (HR) were obtained at the fourth minute to the last minute of exercise. Patients were also characterized on demographic measures, cardiovascular risk factors, baseline exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 38 publications
1
27
0
2
Order By: Relevance
“…The current consensus is that treadmill walking and supine plantar flexion elicit augmented HR and MAP response in patients with PAD compared with control subjects (2,3,11,20,31). Importantly, those patients with higher exercise BP have a higher risk of adverse cardiovascular events (10,11,17,40).…”
Section: Discussionmentioning
confidence: 99%
“…The current consensus is that treadmill walking and supine plantar flexion elicit augmented HR and MAP response in patients with PAD compared with control subjects (2,3,11,20,31). Importantly, those patients with higher exercise BP have a higher risk of adverse cardiovascular events (10,11,17,40).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that the episodes of ischemia produced by walking throughout the monitoring period have influenced this response. Previous studies showed that PAD patients have exaggerated cardiovascular responses during walking [3839], which have been attributed to an activation of pressor reflex caused by ischemia in lower limbs. This response might oppose the hypotensive effect of previous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The time course of the reduction in ankle systolic blood pressure after treadmill exercise from the resting baseline value was quantified by calculating the area under the curve. Because the ischemic window is a function of both PAD severity and the amount of exercise performed, the ischemic window was normalized per meter walked 21 .…”
Section: Methodsmentioning
confidence: 99%